2017
DOI: 10.1371/journal.pone.0174025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tn5 and Sleeping Beauty for transpositional transgenesis by cytoplasmic injection into bovine and ovine zygotes

Abstract: Transgenic domestic animals represent an alternative to bioreactors for large-scale production of biopharmaceuticals and could also provide more accurate biomedical models than rodents. However, their generation remains inefficient. Recently, DNA transposons allowed improved transgenesis efficiencies in mice and pigs. In this work, Tn5 and Sleeping Beauty (SB) transposon systems were evaluated for transgenesis by simple cytoplasmic injection in livestock zygotes. In the case of Tn5, the transposome complex of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…This study also reported that shRNA mediated by the Sleeping Beauty transposon achieved an increased integration rate over random integration of anti- VP1 shRNA. Furthermore, Sleeping Beauty transposase and Tn5 transposase were cytoplasmically injected into sheep zygotes to integrate transposon containing recombinant human factor IX (rhFIX) driven by the BLG promoter (Bevacqua et al, 2017). No transgenic lambs have been obtained from Tn5 transposase injection, while injection of Sleeping Beauty transposase resulted in two lambs that carried the transgene 2/7 (29%) (Bevacqua et al, 2017).…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…This study also reported that shRNA mediated by the Sleeping Beauty transposon achieved an increased integration rate over random integration of anti- VP1 shRNA. Furthermore, Sleeping Beauty transposase and Tn5 transposase were cytoplasmically injected into sheep zygotes to integrate transposon containing recombinant human factor IX (rhFIX) driven by the BLG promoter (Bevacqua et al, 2017). No transgenic lambs have been obtained from Tn5 transposase injection, while injection of Sleeping Beauty transposase resulted in two lambs that carried the transgene 2/7 (29%) (Bevacqua et al, 2017).…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…The most hyperactive SB transposase version currently available, SB100X, displays a $100fold hyperactivity compared with the originally resurrected transposase [50]. The SB100X transposase enables highly efficient germline transgenesis in relevant mammalian models, including mice, rats, rabbits, pigs, sheep, and cattle [51][52][53][54][55][56]. Moreover, the use of the SB100X system yielded robust gene transfer efficiencies into human HSCs [50,57], mesenchymal stem cells, muscle stem/progenitor cells (myoblasts), induced pluripotent stem cells (iPSCs) [58], and T cells [59], which are relevant targets for regenerative medicine and gene-and cell-based therapies of complex genetic diseases.…”
Section: Glossarymentioning
confidence: 99%
“…Previous studies have successfully conducted transposon-based gene delivery to embryos using SB and Tol2 (a transposon derived from fishes) via CPI of a combination of a plasmid DNA (encoding Trans) and a transposon DNA (carrying GOI) to generate Tg animals from bovines [50], pigs [51][52][53], sheep [50], and mice [54]. For example, Garrels et al [51] co-injected a plasmid DNA coding for SB-based hyperactive Trans called SB100X and a transposon plasmid DNA into the cytoplasm of porcine zygotes and obtained Tg fetuses and piglets with high efficiencies (7.5%; 9/120 of transferred embryos).…”
Section: Figurementioning
confidence: 99%